Cost-effectiveness of kinase inhibitors for hematologic malignancies: a systematic and critical review. (3rd September 2017) - Marchetti, Monia
ABSTRACT: Introduction : Several genetic disruptions lead to constitutive activation of those kinases leukemic cells depend on for survival and proliferation. Kinase inhibitors (KI) are major therapeutic innovations for chronic myeloid leukemia (CML), chronic lymphoid leukemia (CLL) and myelofibrosis (MF) providing a relevant improvement of quality-adjusted survival in patients with high-risk or refractory disease. CML patients are being treated with first-generation KI imatinib since many years, achieving expected survivals longer than 10 years. Second- and third generations KIs, such as nilotinib, dasatinib, ponatinib and bosutinib, recently expanded the therapeutic yield for CML and treatment discontinuation in patients with persistent deep molecular response is being pursued. Areas covered : This review summarizes available evidence on economic analyses of KI treatments for CML, CLL and MF aimed at identifying the key determinants of KI cost-effectiveness. Expert commentary : On converse, specific KIs for CLL and MF patients have been marketed only in the last few years. Ibrutinib and idelalisib allowed to improve the outcomes of relapsed/refractory CLL and of patients with poor genetic features, while the first-in-class JAK2 inhibitor ruxolitinib allowed to improve symptoms of advanced MF patients and to prolong survival in responders. In the current situation of healthcare budget restrictions worldwide, the value for cost of the above KIs has been questioned.